Advanced oxidation processes for recalcitrant compounds removal comparison with biofiltration by Corbicula fluminea - Gomes, João (2020)
Conventional treatments cannot remove the emerging contaminants due to their refractory character, therefore improved methodologies should be applied for obtaining their total removal. The need of development of suitable technologies to treat these recalcitrant compounds is related with the wastewater reclamation. Advanced oxidation technologies such as photocatalysis and ozonation appear as suitable solutions for recalcitrant compounds removal. Moreover, the biofiltration can be applied as a pest management approach integrated with wastewater treatment. Due to the invasive character of Corbicula fluminea their usage as biofilter hosts can work as a reduction of their impact over native species or industrial damage. These methodologies were used to promote the degradation of a mixture of SMX, CBZ and LRZ at initial concentration of 1 mg/L of each one. Single ozonation was capable to remove totally SMX and CBZ in 5 min. Whereas only 50% of LRZ were removed in 60 min. The weather can affect the sunlight radiation photon flux which will promote impact on the photocatalytic oxidation using 1 wt% of Ag and Pd-TiO2 as catalysts, for SMX, CBZ and LRZ abatement. C. fluminea was capable to remove about 30% of CBZ and LRZ in 24h.